2019
DOI: 10.3390/coatings9010027
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Growth on Coated Wood Exposed Outdoors: Influence of Coating Pigmentation, Cardinal Direction, and Inclination of Wood Surfaces

Abstract: Four coating systems were exposed for one year outdoors at 45° south. They consisted of solventborne (alkyd based) and waterborne (acrylic based) systems in both clear and pigmented versions. Fungal growth visually assessed was compared to fungal enumeration, and the influence of exposure time on the main fungal species was studied. Results clearly showed that fungal growth was lower on the pigmented coating systems compared with their pigment-free versions. Although the clear solventborne coating included a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The results of surface hardness in Figure 4a show that accelerated weathering increased the surface hardness of coated untreated and heat-treated ash wood samples. A number of authors also found an increase in the surface hardness of wood coated with an acrylic water-based coating after weathering [30][31][32]. The obtained increase in the hardness of the coated wood surface under the influence of accelerated weathering can be related to structural changes and crosslinking in coatings caused by UV radiation, which was determined for free films of emulsion coatings [26].…”
Section: Surface Hardness and Dry Film Thicknessmentioning
confidence: 85%
“…The results of surface hardness in Figure 4a show that accelerated weathering increased the surface hardness of coated untreated and heat-treated ash wood samples. A number of authors also found an increase in the surface hardness of wood coated with an acrylic water-based coating after weathering [30][31][32]. The obtained increase in the hardness of the coated wood surface under the influence of accelerated weathering can be related to structural changes and crosslinking in coatings caused by UV radiation, which was determined for free films of emulsion coatings [26].…”
Section: Surface Hardness and Dry Film Thicknessmentioning
confidence: 85%
“…It has previously been reported that the cardinal direction of exposure affects the colour and chemical changes in the wood due to weathering [19,[34][35][36]. Few reports are available on the effects of cardinal direction on fungal growth and/or associated surface discolouration [14,36]. To investigate this, samples exposed in all directions were swabbed and colony forming units (CFUs) were counted (Figure 2).…”
Section: Microbial Burden Across Cardinal Directionsmentioning
confidence: 99%
“…In long-term experiments, Aureobasidium sp., a polyextremotolerant fungus [52], has consistently been shown to be the prevalent species on wood-based materials [14,17,36]. Podgorski et al, who performed sampling every 3 months, reported that the diversity of fungal species decreases over time and that it is after 9 months that Aureobasidium sp.…”
Section: Dominant Speciesmentioning
confidence: 99%
See 2 more Smart Citations